Is there a perfect way for food security measurement? Evaluation for Turkey - Keskin, Berkay; Demirbaş, Nevin (Progress in Nutrition, 2022)
Even though food security is not a new topic, it is currently a global issue which is a matter of great concern especially in underdeveloped and developing countries. Discussions are ongoing as to how food security can be measured effectively due to the multidimensionality of the issue. The main objective of this study was to review the major methods used to measure food security and evaluate their applicability for Turkey. In this study, case studies in which these methods were applied as well as the possibilities for using these in Turkey were discussed. Although Turkey is among upper-middle income countries, it is a critical country for food security measurement due to the inequity in income distribution and socio-economic differences between the regions. For this reason, instead of applying solitary macro measurements, such as FAO method, using them along with a variety of micro measurements is considered to be more effective for Turkey. This study provides recommendations for governments and social organizations for developing policies and programs focused on solving public problems related to food security both in Turkey and other similar countries.